Galectin-3 in acute myocardial infarction: from molecular mechanisms to clinical translation - Liu, Tingting; Yang, Fang (Frontiers in Molecular Biosciences, 2025)
IntroductionAcute myocardial infarction is a leading cause of global morbidity and mortality. Galectin-3, a β-galactoside-binding lectin, has been implicated as a key mediator in the pathophysiology following AMI. This review aims to synthesize the evidence on the multifaceted role of galectin-3, spanning from molecular mechanisms to clinical applications.MethodsA comprehensive literature review was conducted to synthesize current evidence on the molecular functions, biomarker utility, and therapeutic targeting of galectin-3 in AMI. The analysis focused on studies investigating its signaling pathways, clinical correlations, and preclinical interventional models.ResultsOur synthesis demonstrates that galectin-3 acts as a damage-associated molecular pattern that drives critical post-AMI pathologies. Mechanistically, it amplifies inflammation via NF-κB activation and macrophage polarization, promotes fibrosis through synergy with the TGF-β/Smad pathway and fibroblast activation, and regulates cardiomyocyte apoptosis and oxidative/endoplasmic reticulum stress. Clinically, its dynamic expression correlates with infarct size, adverse ventricular remodeling, and poor outcomes. As a biomarker, elevated circulating galectin-3 predicts major adverse cardiovascular events, heart failure, and mortality, improving risk stratification in multi-marker panels. Serial measurements indicate treatment response, with declining levels post-PCI or statin therapy associated with improved prognosis. Therapeutically, both genetic ablation and pharmacological inhibition of galectin-3 attenuate inflammation, fibrosis, and cardiac dysfunction in preclinical models.DiscussionGalectin-3 occupies a critical position at the intersection of AMI pathogenesis, diagnosis, and therapy. Targeting the galectin-3 pathway represents a promising therapeutic strategy to improve post-AMI outcomes, although its clinical translation requires further investigation. This review underscores the potential of integrating galectin-3 assessment and inhibition into future AMI management strategies.